2015
DOI: 10.1016/j.apnr.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of an exercise counseling intervention using motivational interviewing

Abstract: Aim To describe the results of the process evaluation of an exercise counseling intervention using motivational interviewing (MI). Background Exercise can safely be incorporated into heart failure self-care, but many lack access to cardiac rehabilitation. One alternative is to provide exercise counseling in the clinical setting. Methods This process evaluation was conducted according to previously established guidelines for health promotion programs. This includes an assessment of recruitment and retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
0
20
0
5
Order By: Relevance
“…16 studies were RCT’s [ 32 – 48 ] and five were one arm (pre-post) trials [ 49 53 ]. All studies reported some form of behavioural support which aimed to increase the uptake of physical activity (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…16 studies were RCT’s [ 32 – 48 ] and five were one arm (pre-post) trials [ 49 53 ]. All studies reported some form of behavioural support which aimed to increase the uptake of physical activity (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…information about health benefits, goal setting, self-monitoring, and pedometers). Studies used motivational interviewing (MI) [ 34 , 37 , 39 , 48 , 52 , 53 ], Cognitive Behaviour Therapy (CBT) [ 39 ], and guided self-management based on a range of theoretical approaches including social cognitive theory (SCT) [ 36 , 44 , 48 , 50 , 51 ], theory of planned behaviour (TPB) [ 47 , 51 ], self-determination theory (SDT) [ 37 , 41 , 43 ], the trans-theoretical model (TTM) [ 36 , 39 , 40 , 42 , 47 ] and self-regulation theory [ 38 , 46 ]. Physical activity was assessed using self-report [ 32 – 34 , 36 , 37 , 39 – 41 , 44 , 47 , 48 , 50 , 52 ], or objective measures of physical activity (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations